From Reactive Regulation to Preventive Governance: A Pancasila-Based Legal Framework for Child Marriage Prevention in Central Lombok - Abdul Wahab; Yorman (Bulletin of Community Engagement, 2026)
This study advances a Pancasila-based preventive governance framework for addressing child marriage by integrating empirical evidence from adolescent pregnancy data in Central Lombok, Indonesia. Using an empirical socio-legal research design, the study analyzes population-based administrative records of pregnancies and childbirths among girls under 19 years of age collected from all primary health centers (puskesmas) between 2022 and 2024. Adolescent pregnancy is employed as a policy-relevant empirical proxy for child marriage, reflecting the close structural linkage between underage unions and early childbearing in low- and middle-income contexts. The findings demonstrate that while the overall incidence of adolescent pregnancy declined after 2022, the childbirth-to-pregnancy ratio increased steadily, indicating the persistence of social and institutional mechanisms that normalize early marriage following pregnancy. Marked spatial inequalities were also identified, with specific health service regions consistently bearing a disproportionate burden of adolescent pregnancy and childbirth. These empirical patterns reveal that Indonesia’s minimum-age marriage regulation continues to function predominantly as a reactive legal instrument, addressing consequences rather than preventing risk exposure. Normatively, the study argues that this condition reflects a failure of legal governance to substantively safeguard children’s dignity and realize social justice. By reconstructing child marriage prevention through the Pancasila principles of humanity, social justice, participatory governance, and social solidarity, the study proposes a preventive legal framework that operationalizes routine health data as an early-warning system, strengthens community participation, and enables region-based governance interventions. Methodologically, the study demonstrates how administrative health data can be transformed into actionable legal indicators, while substantively contributing to socio-legal scholarship on preventive governance and offering policy-relevant insights for sustainable child marriage prevention in plural legal systems.